Post-Mastectomy Breast Reconstruction: Exploring Plastic Surgeon Practice Patterns and Perspectives - Momoh, Adeyiza O (Plast Reconstr Surg, 2020)
BACKGROUND: Within the multidisciplinary management of breast cancer, variations exist in the reconstructive options offered and care provided. This study aimed to evaluate plastic surgeon perspectives on important issues related to breast cancer management and reconstruction and provide some insight into factors that influence these perspectives. METHODS: Women diagnosed with early stage breast cancer (stages 0-II) between July 2013 and September 2014 were identified through the Georgia and Los Angeles SEER registries. These women were surveyed and identified their treating plastic surgeons. Surveys were sent to the identified plastic surgeons to collect data on specific reconstruction practices. RESULTS: Responses from 134 plastic surgeons (74.4% response rate) were received. Immediate reconstructions (79.7%) was the most common approach to timing, and expander/implant reconstructions (72.6%) was the most common technique reported. Nearly a third (32.1%) of respondents reported that reimbursement influenced the proportion of autologous reconstructions performed. Most (82.8%) reported that discussions about contralateral prophylactic mastectomy were initiated by patients. Most surgeons (81.3%-84.3%) felt that good symmetry is achieved with unilateral autologous reconstruction with contralateral symmetry procedures in patients with small or large breasts; a less pronounced majority (62.7%) favored unilateral implant reconstructions in patients with large breasts. In patients requiring post-mastectomy radiation, a quarter of the surgeons (27.6%) reported that they seldom recommend delayed reconstruction, and 64.9% reported recommending immediate expander/implant reconstructions. CONCLUSIONS: Reconstructive practices in a modern cohort of plastic surgeons suggests that immediate and implant reconstructions are performed preferentially. Respondents perceived a number of factors, including surgeon training, time spent in the operating room and insurance reimbursement, to negatively influence the performance of autologous reconstruction.